Poetry of Ruqshaana Kamish - Kamish, Ruqshaana (WritingThreeSixty: Journal or Research and Creative Text, 2021)
Rebellion Love’s folly Disillusioned Journey towards life Broken wings Leap of faith Separate paths More than this Crossing boundaries Falling into you Essence of a poet With clearer eyes Just hello Unforgettable Destiny Worlds apart Limitless The edge Green market square Doomed love Echoes Sins of the father Fight for sanity I say Elements of freedom Mystery Fundamental nature Melody Canvas of life The heart of mankind Utter stupidity Long forgotten Lonely man Cynical love